Identification of competitive high yielding and stress tolerant demand-driven common bean varieties for key agro-ecologies and cropping systems in East and Southern Africa - Mukankusi, Clare; Mamo, Teshale Assefa; Nkhata, Wilson; Amongi, Winnyfred; Nkalubo, Stanley; Kilango, Michael; Mbiu, Julius; Misango, Shamir; Antonio, David; Chisale, Virginia (2023)
The Alliance of Bioversity and CIAT through Pan Africa Bean Research Alliance (PABRA) supported ten national bean breeding programs that included Department of Agriculture Research Services (DARS) -Malawi, Tanzania Agriculture Research Institute (TARI-Uyole)-Tanzania, National Research Agronomic Research Institute (AII) Botswana, National Agriculture Research Development Institute (NARDC) Angola in the Southern Africa Bean Research Network (SABRN) and Tanzania Agriculture Research Institute (TARI-Maruku), Tanzania Agriculture Research Institute (TARI-Selian), Kenya Agricultural and Livestock Research Organization (KARLO-Kakamega), National Agricultural Crops Research Resources institute (NACRRI-Uganda) and the Ethiopia Institute of Agricultural Research (EIAR-Melkassa), to select new bean varieties that are suitable for the diverse agro-ecologies and cropping systems. New breeding lines were tested from the PABRA2023 regional trial for multilocational trialing, whole candidates were also evaluated at preliminary and advanced stages and candidates for release identified.